2007
DOI: 10.1111/j.1937-5956.2007.tb00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Inventory Record Inaccuracy, Double Marginalization, and RFID Adoption

Abstract: Most retailers suffer from substantial discrepancies between inventory quantities recorded in the system and stocks truly available to customers. Promising full inventory transparency, radio frequency identification (RFID) technology has often been suggested as a remedy to the problem. We consider inventory record inaccuracy in a supply chain model, where a Stackelberg manufacturer sets the wholesale price and a retailer determines how much to stock for sale to customers. We first analyze the impact of invento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(127 citation statements)
references
References 20 publications
4
123
0
Order By: Relevance
“…They showed that the incentives of the parties for investing in RFID are not perfectly aligned in the existence of the fixed cost of investment. Heese [33] investigated the effect of inventory inaccuracy on supply chain performance and the impact of double marginalization on the parties' incentives for RFID adoption. They showed that RFID adoption improves supply chain coordination and a decentralized supply chain can benefit more from RFID technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They showed that the incentives of the parties for investing in RFID are not perfectly aligned in the existence of the fixed cost of investment. Heese [33] investigated the effect of inventory inaccuracy on supply chain performance and the impact of double marginalization on the parties' incentives for RFID adoption. They showed that RFID adoption improves supply chain coordination and a decentralized supply chain can benefit more from RFID technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Order was generated using the new information system linked to the RFID technology. [11][12][13][14][15][16] In Model 3 (automated delivery) or AGV Model, inventory checking, picking and replenishment at service points were manual, order was generated by manually keying in the existing hospital information system while transportation was automated using AGVs. Detailed comparison of the 3 models in terms of process is depicted in Table 3.…”
Section: Details Of Interventionsmentioning
confidence: 99%
“…Item-level information visibility is analytically analyzed by Zhou [117]. Inventory-record inaccuracy in a supply chain model is discussed by Heese [57]. A simulation-based framework for evaluating the effect of inventory error on the performance of complex distribution systems was developed by Goebel and Günther [51], which allows one for comparing the profitability of RFID for inventory tracking with other managerial measures.…”
Section: Rfid In the Supply Chain -Towards An "Internet Of Things"mentioning
confidence: 99%